Parâmetros genéticos do peso adulto e características de desenvolvimento ponderal na raça Nelore - Pedrosa, Victor Breno; Eler, Joanir Pereira; Ferraz, José Bento Sterman; Silva, Josineudson Augusto II de Vasconcelos; Ribeiro, Sandra; Silva, Márcio Ribeiro [UNESP]; Pinto, Luis Fernando Batista (My University, 2010)
The animal breeding programs of beef cattle in Brazil have focused on selection for weight traits due to the fact that they are measures easily obtained. Within this context, it was analyzed data of 74,547 animals to evaluate the mature weight (MW) and the mature weight with repeated measurements (MWr) in Nellore animals. Heritability coefficients were estimated for mature weight and for other growth traits as post-weaning weight (PW), conformation (CONF), precocity (PREC), musculature (MUSC) and hip height (HH). The genetic correlation between those traits was also estimated. The (co)variances components were estimated by the Restricted Maximum Likelihood Multiple Trait Derivative Free method (MTDFREML), using the complete animal model. The estimates of heritability coefficients were 0.43 for MW and 0.41 for MWr; 0.38 for PW, 0.23 for CONF, 0.19 for PREC, 0.22 for MUSC and 0.35 for HH. The genetic correlation coefficients ranged from 0.37 to 0.70. The heritability coefficients suggest that mature weight may respond to selection and be used to monitor the size of females from the Nellore breed. The genetic correlation coefficients between mature weight and other growth traits were high and positive, indicating that selection for mature weight influences the performance of the other studied traits.

Os programas de melhoramento genético de gado de corte, no Brasil, têm priorizado a seleção para características de peso, por serem medidas de fácil obtenção. Dentro desse contexto, foram analisados dados de 74.547 animais com o objetivo de avaliar o peso adulto (PAV) e o peso adulto como medida repetida (PAVr) em animais Nelore. Foram estimados coeficientes de herdabilidade para peso adulto e para outras características de desenvolvimento ponderal, como peso ao sobreano (PS), conformação (CONF), precocidade (PREC), musculosidade (MUSC) e altura na garupa (AG). Estimou-se também a correlação genética entre essas características. Os componentes de (co)variâncias foram estimados pelo método de máxima verossimilhança restrita (MTDFREML) por meio do modelo animal completo. As estimativas dos coeficientes de herdabilidade foram de 0,43 para PAV e 0,41 para PAVr; 0,38 para PS; 0,23 para CONF; 0,19 para PREC; 0,22 para MUSC e 0,35 para AG. Os coeficientes de correlação genética obtidos variaram de 0,37 a 0,70. Os coeficientes de herdabilidade obtidos sugerem que o peso adulto pode responder à seleção e ser utilizado para o monitoramento do tamanho das fêmeas na raça Nelore. Os coeficientes de correlação genética entre peso adulto e as demais características de desenvolvimento ponderal foram altos e positivos, o que indica que a seleção para o peso adulto influencia o desempenho das outras características estudadas.
Genetic parameters for mature weight and growth traits in Nelore cattle
Keywords: Animal breeding; Beef cattle; Mature weight; Performance traits; Zebu cattle; Bovinos de corte; Características produtivas; Melhoramento genético; Tamanho adulto; Zebuínos